2003
DOI: 10.1007/s00117-003-0885-8
|View full text |Cite
|
Sign up to set email alerts
|

Bildgebung bei neuroendokrinen Tumoren des Pankreas

Abstract: None of the various modalities is superior alone, so that it is often necessary to combine them for diagnostic imaging of pancreatic islet cell tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…31 Therefore, the diagnostic accuracy of dynamic CT is insufficient, with 64-81% of sensitivity. 32 In our study, only 67% of Some reports have shown that tumor-to-pancreas contrast is usually greatest in the arterial phase in PNEN cases. 17,18,20,31 Therefore, we used arterial phase images to evaluate the enhancement and calculate the CT ratio.…”
Section: Discussioncontrasting
confidence: 54%
“…31 Therefore, the diagnostic accuracy of dynamic CT is insufficient, with 64-81% of sensitivity. 32 In our study, only 67% of Some reports have shown that tumor-to-pancreas contrast is usually greatest in the arterial phase in PNEN cases. 17,18,20,31 Therefore, we used arterial phase images to evaluate the enhancement and calculate the CT ratio.…”
Section: Discussioncontrasting
confidence: 54%
“…NET cells are characterized by an increased expression of somatostatin receptors, making somatostatin receptor imaging a promising option for detecting NET. 16 21 In-111 DTPA octreotide SPECT/CT is currently the standard technique for performing somatostatin receptor imaging. 22 A promising alternative is somatostatin receptor PET/CT using tracers such as Ga-68 DOTATOC, Ga-68 DOTATATE, or Ga-68 DOTANOC.…”
Section: Introductionmentioning
confidence: 99%